2011
DOI: 10.1039/c1cc12253c
|View full text |Cite
|
Sign up to set email alerts
|

A zinc(ii) metal–organic framework based on triazole and dicarboxylate ligands for selective adsorption of hexane isomers

Abstract: A three-dimensional (3D) metal-organic framework {[Zn(2)(HBDC)(2)(dmtrz)(2)]·guest}(n) with pcu net has been solvothermally synthesized, which shows selective adsorption of linear and monobranched hexane isomers over a dibranched one.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
36
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 55 publications
0
36
0
Order By: Relevance
“…Zhao et al evaluated the adsorption of nHEX, 3MP, and 22DMB on Zn 2 (Hbdc) 2 (dmtrz) 2 (H 2 bdc = 1,4‐benzenedicarboxylic acid, Hdmtrz = 3,5‐dimethyl‐1H,1,2,4‐triazole). [ 100 ] The MOF possesses 1D channels with diameter of 6.7 Å. Single‐component vapor adsorption isotherms revealed that it adsorbs similar amounts of nHEX (13.3 wt%) and 3MP (12.1 wt%), but substantially less 22DMB (3.5 wt%). Gas chromatography measurements using a Zn 2 (Hbdc) 2 (dmtrz) 2 ‐filled column indicated that 22DMB was nicely separated from the other two isomers.…”
Section: Separation Of Alkane Isomersmentioning
confidence: 99%
“…Zhao et al evaluated the adsorption of nHEX, 3MP, and 22DMB on Zn 2 (Hbdc) 2 (dmtrz) 2 (H 2 bdc = 1,4‐benzenedicarboxylic acid, Hdmtrz = 3,5‐dimethyl‐1H,1,2,4‐triazole). [ 100 ] The MOF possesses 1D channels with diameter of 6.7 Å. Single‐component vapor adsorption isotherms revealed that it adsorbs similar amounts of nHEX (13.3 wt%) and 3MP (12.1 wt%), but substantially less 22DMB (3.5 wt%). Gas chromatography measurements using a Zn 2 (Hbdc) 2 (dmtrz) 2 ‐filled column indicated that 22DMB was nicely separated from the other two isomers.…”
Section: Separation Of Alkane Isomersmentioning
confidence: 99%
“…120 There exist one-dimensional channels of 7.0 60 × 7.0 Å along the c axis. Compared to the selective adsorption of nhex over 3mP on [Zn 2 (bdc) 2 (dabco)], this material shows no obvious selective adsorption between these two isomers.…”
Section: Separation Of Hexane Isomersmentioning
confidence: 99%
“…gathers some data on the adsorption performance of different materials such as carbons, zeolites, MOFs, and zeolitic imidazolate frameworks (ZIFs) tested for the separation of C 6 isomers compared to those of the tannin-derived MMCs of this study[4,[20][21][22]58,65,66]. Even more, to directly compare the C 6 separation performance of the present MMCs derived from MT extract with that of MOFs used for gas separation, IAST calculations were performed using the single-component adsorption isotherms of HKUST-1, UiO-66, and ZIF-8, previously reported by Cuadrado-Collados et al[58].…”
mentioning
confidence: 99%